Detection of circulating DNA for the diagnosis of invasive fusariosis: retrospective analysis of 15 proven cases. (31st August 2022) - Dellière, Sarah; Guitard, Juliette; Sabou, Marcela; Angebault, Cécile; Moniot, Maxime; Cornu, Marjorie; Hamane, Samia; Bougnoux, Marie-Elisabeth; Imbert, Sébastien; Pasquier, Grégoire; Botterel, Françoise; Garcia-Hermoso, Dea; et al.
Abstract: Fusarium spp. are plant pathogens and opportunistic pathogens in severely immunocompromised (hematological malignancy, neutropenia, solid organ transplantation, etc.) and severely burned patients. Invasive fusariosis often disseminates and mortality remains high partly due to delayed diagnosis in the absence of a positive culture. The aim of our study is to design a quantitative PCR (qPCR) assay and evaluate the detection of Fusarium spp. DNA for early diagnosis of invasive infection. A qPCR assay was designed and optimized to identify all Fusarium species complex and secondarily evaluated on patient samples. A total of 81 blood samples from 15 patients diagnosed with proven invasive fusariosis from 9 centers in France were retrospectively tested. Circulating DNA was detected in 14 patients out of 15 (sensitivity of 93% [95% Confidence Interval (CI95), 70.1-99.7]). Detection was possible up to 18 days (median 6 days) before the diagnosis was confirmed by positive blood culture or biopsy. By comparison serum galactomannan and ß-D-glucan were positive in 7.1 and 58.3% of patients respectively. qPCR was negative for all patients with other invasive fungal diseases (IFD) tested ( n  = 12) and IFD-free control patients ( n  = 40). No cross-reactions were detected using DNA extracted from 81 other opportunistic fungi. We developed and validated a pan- Fusarium qPCR assay in serum/plasma with high sensitivity, specificity, and reproducibility that could facilitate early diagnosis and treatment monitoring of invasive fusariosis. Lay Abstract: Fusariosis ranks third among invasive mould infections. It is frequently diagnosed late due to the lack of specific tools. We designed and evaluated a new qPCR assay with high sensitivity and specificity allowing detection of Fusarium DNA in serum samples up to 18 days before conventional diagnosis.